Microglia Are Essential to Protective Antiviral Immunity: Lessons From Mouse Models of Viral Encephalitis - Hatton, Catherine F.; Duncan, Christopher J. A. (Frontiers in Immunology, 2019)
Viral encephalitis is a rare but clinically serious consequence of viral invasion of the brain and insight into its pathogenesis is urgently needed. Important research questions concern the involvement of the host innate immune response in pathogenesis, key to which is the role played by microglia, resident macrophages of the brain parenchyma. Do microglia have a protective function, by coordinating the innate immune response to viral infection, or do they drive pathogenic neuroinflammation? Here we synthesise recent data from mouse models of acute viral encephalitis, which reveal an unambiguously protective role for microglia. Depletion of microglia, via blockade of colony stimulating factor 1 receptor (CSF1R) signalling, led to increased viral replication accompanied by more severe neurological disease and heightened mortality. Whilst the underlying mechanism(s) remain to be defined, microglial interactions with T cells and phagocytosis of infected neurones appear to play a role. Paradoxically, the production of inflammatory cytokines was increased in several instances following viral infection in microglia-depleted brains, suggesting that: (i) cells other than microglia mediate inflammatory responses and/or (ii) microglia may exert a regulatory function. In addition, under certain circumstances the microglial antiviral response might contribute to long-term neurological sequelae. Understanding microglial regulation in encephalitis is therefore a priority for future studies. Collectively, these findings demonstrate the central role of microglia in pathogenesis, suggesting the exciting possibility that defects of microglial function might contribute to encephalitis susceptibility and/or outcome in humans.